SENI LUKIS DEWA PUTU MOKOH PASCA RUDOLF BONNET - Putra, I Gusti Ngurah; Sukarya, I Wayan (Program Studi Seni Murni ISI Bali, 2021)
The presence of two Western painter Walter Spies, Rudolf Bonnet community of artists make very high antosias studied painting so by Cokorda Gede Sukawati build bevy of artists deemed necessary to ensure the welfare of the artists, so stand Pita Maha (1932) means a great soul or creativity. Dewa Putu Mokoh is the only young artists at that time who had the courage to come out of the themes puppet. Mokoh no longer presents the themes puppet as painted by the artists of that time. In addition, the courage to lift sex life through the development of techniques and approaches the theme of sex in humorous narrative. Factors that influence the work of Mokoh ie, natural, social, cultural, religious, education and tourism. In the presence of all influences interact and coalesce and grow into love in its development that is supported by the skills and professional. In addition, the work serves as a work Mokoh aesthetic, renewal, education, economy and to decorate the space, in his form with regard to aesthetic function. Impact Mokoh paintings that contribute new ideas, creative economy, namely the growth sectors of business life, giving birth to new artists who have the courage to give birth to works of art are bold, unique, interesting and has a distinctive character or trait. In addition, painting Mokoh have a different meaning, namely the symbolic meaning, the meaning relegi, meaning renewal, cultural significance, and reflection. Painting Dewa Putu Mokoh although express object of reality, which is seen directly, but there is a message and a specific meaning to be conveyed. To understand the symbolic paintings Dewa Putu Mokoh implied through the realization of painting, the symbolic meaning.